Analisis Pengendalian Piutang Pada PT Teguh Jaya Abadi Sentosa cabang Samarinda Tahun 2014-2018 - relita sihombing; Elfreda Aplonia Lau; Rina Masitoh Haryadi (Exchall: Economic Challenge, 2021)
PT Teguh Jaya Abadi Sentosa Samarinda conducts sales in cash and on credit. Sales on credit generate accounts receivable. Sales on credit continue to increase so that accounts receivable continues to grow, thus it is necessary to control accounts receivable. This study aims to determine and analyze the Receivable Control at PT Teguh Jaya Abadi Sentosa 2014-2018 Samarinda based on Receivable Turn Over, Average Collection Period, Accounts Arrears and Receivables collection Ratio with the formulation of the problem is the control of receivables. The result showed that the Receivable Turn Over from 2014-2018 decreased, which means that there was a decrease in accounts receivable control. Likewise, the Average Collection period from 2014-2018 continuesly increase as a sign of a decline in receivable control.The result also show that the ratio of arrears from 2014-2018 has increased, it means there is a decrease in receivable control, as well as the Receivable collection ratio continuesly decline from 2014-2018, which shows a decrease in accounts receivable control. Overall, these findings indicate that the control of PT Teguh Jaya Abadi Sentosa's receivables in 2014-2018 has decreased.Keywords: Accounts Receivable, Receivable Turn Over, Average Collection Period, Arrears Ratio, Collection Ratio